2019
DOI: 10.1016/j.soard.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of suicide-related thoughts and behaviors among bariatric surgery patients

Abstract: Background: Past research suggests self-harm/suicidality are more common among adults who have undergone bariatric surgery than the general population.Objectives: To compare prevalence of self-harm/suicidal ideation over time and identify presurgery risk factors for post-surgery self-harm/suicidal ideation. Setting:The Longitudinal Assessment of Bariatric Surgery-2 is a cohort study with pre-surgery and annual post-surgery assessments conducted at ten US hospitals.Methods: Adults with severe obesity undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
0
33
2
3
Order By: Relevance
“…Four years after treatment initiation, 3.7% in the surgical group and 11.5% in the non-surgical group reported any current suicidal ideation according to BDI-2. The frequency was also higher than in previous findings in adults after MBS, where 6.6% reported self-harm/suicidal ideation at the 5-year follow-up [43]; however, the frequency is about the same as that reported by participants in the same sample at the 2-year follow-up [44].…”
Section: Discussioncontrasting
confidence: 70%
“…Four years after treatment initiation, 3.7% in the surgical group and 11.5% in the non-surgical group reported any current suicidal ideation according to BDI-2. The frequency was also higher than in previous findings in adults after MBS, where 6.6% reported self-harm/suicidal ideation at the 5-year follow-up [43]; however, the frequency is about the same as that reported by participants in the same sample at the 2-year follow-up [44].…”
Section: Discussioncontrasting
confidence: 70%
“…13 Being male was also shown to predict a higher risk of self-harm/suicidal ideation in the 5 years after surgery. 27 In the general population, a "gender paradox of suicidal behavior" has been reported: completed suicide is more prevalent in men, while non-fatal self-harm is more prevalent in women. 28 Although we were not able to analyze these two outcomes separately (due to a low number of completed suicides: 7 in men and 6 in women), it is still possible that some of the mechanisms proposed to explain this gender paradox are relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have documented increased risk of suicide in individuals with severe obesity . A LABS‐2 study that included 2,217 patients with 5 years of follow‐up found that before bariatric surgery, 25% of patients reported a history of suicidal thoughts or behavior, which is considerably higher than in the general population . The prevalence of self‐harm/suicidal ideation was 5.3% before surgery and 3.8% at year 1 post surgery.…”
Section: Mental Health Effects Of Bariatric Surgerymentioning
confidence: 99%